Modern materials for cutting tools and the manufacture of these tools by means of welding - POCHKA, Kostiantyn; SHALENKO, Vadym; KORNIICHUK, Borys; PALAMARCHUK, Dmytro; MASLIUK, Andrii (Ways to Improve Construction Efficiency, 2025)
Industry uses a wide variety of tools that differ significantly in design and operating conditions, depending on their purpose. For machining tools, the most important requirement is high strength and hardness, which ensure high wear resistance. In order to prevent plastic deformation of the working surfaces under the influence of high temperatures, the tool material, along with a high hardness 2…3 times greater than that of the workpiece, must have high heat resistance. Welding plays a key role in the production of combination tools, where the cutting part is welded to a base made of cheaper material, which significantly reduces the cost and improves the performance of the tool. Modern band saws are made from bimetallic compositions. Spring steel is used as the base, to which a narrow strip of high-speed steel is welded. After that, the teeth are cut on a milling machine. This combination solves several problems at once: it increases the fatigue resistance of the saw body; the cutting edge has optimal wear resistance; cutting resistance is minimized. Spring steel grades are selected for the saw body: 45ХН2МФА, 50ХГФА. The cutting edge of the saw is made of high-speed steels of grades 7P1M5K5, 11P2M10K8 (M42 or HSS Co8 (High Speed Steel)) and 12P10M4K10 (M51 or HSS Co10). Band saws and knives can be welded using professional equipment from Ideal Werk, Germany. We have reviewed equipment for manufacturing the latest models of band saws and knives from the BAS 320 and BAS 330 series, equipped with special clamping mechanisms for each type of product, automatic multi-stage weld annealing control, a hydraulic knife for removing weld ridges, and positioning systems. The analysis conducted in this work allows reducing the cost of tool production by using expensive cutting materials only where necessary. Improve the mechanical properties of the tool by combining the hardness of the cutting part with the strength of the base. Expand the range of tool applications by creating combined products for different types of processing.